Clinical Features and Outcomes of Spontaneous Bacterial Peritonitis Caused by Streptococcus pneumoniae: A Matched Case-Control Study - Kim, Taeeun (Medicine (Baltimore), 2016)
Streptococcus pneumoniae is a well-known cause of spontaneous bacterial peritonitis (SBP) in cirrhotic patients. However, little information is available regarding clinical characteristics and outcomes of SBP caused by S. pneumoniae. It has been suggested that spontaneous pneumococcal peritonitis (SPP) often spreads hematogenously from concomitant pneumococcal pneumonia, and is associated with a higher rate of mortality. During the period between January 1997 and December 2013, 50 SPP cases were identified. These cases were then age/sex-matched with 100 patients with SBP due to causes other than S. pneumoniae (controls). SPP accounted for 4.3% (50/1172) of all culture-proven SBPs. The baseline Child-Pugh class, etiology of cirrhosis, and model for end-stage liver disease scores were comparable for the 2 groups. SPP patients were more likely than control patients to have a community-acquired infection (90.0% vs. 76.0%; P = 0.04), concurrent bacteremia (84.0% vs. 59.0%; P = 0.002), and to present with variceal bleeding (10.0% vs. 1.0%; P = 0.02). None of the study patients had pneumococcal pneumonia. The most common initial empirical therapy for both groups was third-generation cephalosporins (96.0% vs. 91.0%; P = 0.34) which was active against a significantly higher proportion of the cases than of the controls (97.8% vs. 78.7%; P = 0.003). Thirty-day mortality was significantly lower in the case group than in the control group (10.0% vs. 24.0%; P = 0.04). SPP was not associated with pneumococcal pneumonia and showed lower mortality than SBP caused by other organisms. However, the present study was constrained by the natural limitations characteristic of a small, retrospective study. Therefore, large-scale, well-controlled studies are required to demonstrate the influence of SPP on mortality, which was marginal in the present study.